The effect of body mass index and stroke length on short freestyle swimming distance - Taskin, M. (International Journal of Applied Exercise Physiology, 2020)
Background: Some basic variables of swimming performance have been described for both females and males, including post time, stroke rate, stroke length, average velocity, height, body weight, and age. Methods: The study aims to investigate the relationship between stroke length (SL) and short swimming distance performance. Total 22 male (mean ± SD: age = 11.36 ± 0.492 yr, height = 1.51 ± 0.084 m, body weight = 44.55 ± 9.821 kg, and body mass index (BMI) = 19.58 ± 3.583 kg/m2) volunteered to participate in the study. A stopwatch was used to measure the speed of swimmers at a distance of 25 meters. Stroke length was evaluated as the distance taken in one cycle. BMI was calculated as mass in kilograms divided by (height in meters)2. Results: SL predicts short swimming distance performance by 29 %. One unit change in SL affects short distance swimming performance by 38.38 percent. Conclusion: It is seen that stroke length positively affects swimming performance in short distance swimming and body mass index is not effective in short distance swimming. It is thought that it is important for the trainers to consider the stroke length for performance in children participating in swimming.